The Study of the Relationship between the Formation of Organizational Loyalty and the Degree of Satisfaction with Work, Locus of Control among Employees in the Organization - Olga Ivanovna SHCHERBAKOVA; Vladimir Viktorovich VELIKOROSSOV; Venera Olegovna MIDOVA; Viktoria SKLYADNEVA; Sergey Alexandrovich FILIN; Ona Grazyna Rakauskiene (Communications of International Proceedings, 2021)
Research Motivation: the article presents an analysis of such concepts in foreign and domestic psychological and pedagogical studies as organizational loyalty (commitment); satisfaction with the work of employees of organizations; external and internal locus of control.  Research Methodology: to identify the features of organizational loyalty of employees, we used the questionnaire of John Meyer and Natalie Allen "The scale of organizational loyalty". With the help of this questionnaire, the severity of affective, normative, and current commitment can be determined. The study of employee satisfaction with work was carried out by using the method "Integral satisfaction with work", the authors of which are Fetiskin N. P., Kozlov V. V., Manuylov G. M. To determine the locus of control of students, we chose the method "Diagnostics of the level of subjective control" by J. Rotter in the adaptation of E. F. Bazhin, S. A. Golynkina, A. M. Etkind. To assess the relationship between the studied phenomena, we used Ch. Spearman’s rank correlation coefficient criterion. Main Findings: the authors show in an empirical study the relationship between organizational loyalty and such individual characteristics of an employee as subjective satisfaction with work and locus of control. The reliability of the results was proved using mathematical methods of processing the obtained data: high internality in the field of achievements has a positive effect not only on the affective loyalty of employees but also on the current and normative organization commitment.
Keywords: Performance Factors; Organizational Loyalty; Commitment; Job Satisfaction; Locus Of Control; Employee Responsibility; Rank Correlation Coefficient.